2019
DOI: 10.3390/ijgi8050230
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation of Heterogeneous Cultural Heritage Objects for the Promotion of Tourism

Abstract: The cultural heritage of a region, be it a highly visited one or not, is a formidable asset for the promotion of its tourism. In many places around the world, an important part of this cultural heritage has been catalogued by initiatives backed by governments and organisations. However, as of today, most of this data has been mostly unknown, or of difficult access, to the general public. In this paper, we present research that aims to leverage this data to promote tourism. Our first field of application focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Some proposals are supported on users' interaction to obtain their data (i.e., following a PULL paradigm). In (Rajaonarivo et al, 2019), authors model the users' information considering their gender, age category (e.g., kid, adult, or elderly), and preferences, classified as thematic preferences (e.g., museum, theater) and historical preferences (e.g., 12th century), that have to be provided by them through a user interface. In (Santos et al, 2019), only health, physical, and psychological conditions are required with forms filled by users.…”
Section: User Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…Some proposals are supported on users' interaction to obtain their data (i.e., following a PULL paradigm). In (Rajaonarivo et al, 2019), authors model the users' information considering their gender, age category (e.g., kid, adult, or elderly), and preferences, classified as thematic preferences (e.g., museum, theater) and historical preferences (e.g., 12th century), that have to be provided by them through a user interface. In (Santos et al, 2019), only health, physical, and psychological conditions are required with forms filled by users.…”
Section: User Informationmentioning
confidence: 99%
“…In order to improve suggestions, the trend is to consider context aspects that describe a specif situation in a determined moment for a user, including transportation media, weather, time, or even health conditions. Many works use context-modeling approaches that mainly consider means of transportation, travel time, location, or weather (Bahramian et al, 2017;Kesorn et al, 2017;Arigi et al, 2018;Logesh et al, 2018;Rajaonarivo et al, 2019;Logesh and Subramaniyaswamy, 2019).…”
Section: Context-awarenessmentioning
confidence: 99%
See 2 more Smart Citations
“…In this early phase of our work we focused on the user experience. At variance in respect to [ 7 , 9 , 10 ], the faceted search, the query results, and the itinerary preview are all shown in the same page, in order to facilitate query insertion and path selection. The SearchPath service is the only tourist application that supports a multi-path preview that enables the users to easily compare and select different paths.…”
Section: Introductionmentioning
confidence: 99%